The efficiency of acoustic radiation force impulse (ARFI) elastography in the diagnosis and staging of carpal tunnel syndrome - USLU, FERDA; Arslan, Harun; Ilgen, Ferda; Yavuz, Alpaslan; Aycan, Abdurrahman; Özgökçe, Mesut; Akdeniz, Hüseyin; Batur, Abdussamet (My University, 2018)
The aim of the present study was to quantify the stiffness of the median nerve (MN) at the carpal tunnel inlet by acoustic radiation force impulse (ARFI) elastography and to evaluate whether ARFI can be used in diagnosis and staging of carpal tunnel syndrome (CTS).